2006
DOI: 10.2337/diacare.29.04.06.dc05-2180
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Among Pain, Sensory Loss, and Small Nerve Fibers in Diabetes

Abstract: OBJECTIVE -Many individuals with diabetes experience neuropathic pain, often without objective signs of large-fiber neuropathy. We examined intraepidermal nerve fibers (IENFs) to evaluate the role of small nerve fibers in the genesis of neuropathic pain.RESEARCH DESIGN AND METHODS -Twenty-five diabetic subjects with neuropathic pain and 13 without were studied. The pain was present for at least 6 months for which no other cause could be found. Punch skin biopsies were obtained from the distal leg. IENFs were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
154
3
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(166 citation statements)
references
References 27 publications
6
154
3
3
Order By: Relevance
“…This finding is, of course, in contrast with several studies that have demonstrated a reduction in IENF density in patients with impaired glucose tolerance, but it must be remembered that these patients also had painful neuropathy (12). Indeed, it may be that pain is related to loss of IENFs as shown in a recent study in which diabetic patients with painful neuropathy had a significant reduction in IENFD compared with diabetic patients with painless neuropathy (29). Several studies have attempted to address whether there is a relationship between the severity of neuropathy and the degree of IENF loss.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This finding is, of course, in contrast with several studies that have demonstrated a reduction in IENF density in patients with impaired glucose tolerance, but it must be remembered that these patients also had painful neuropathy (12). Indeed, it may be that pain is related to loss of IENFs as shown in a recent study in which diabetic patients with painful neuropathy had a significant reduction in IENFD compared with diabetic patients with painless neuropathy (29). Several studies have attempted to address whether there is a relationship between the severity of neuropathy and the degree of IENF loss.…”
Section: Discussioncontrasting
confidence: 53%
“…However, it is important to note that all patients had severe neuropathy as they were undergoing pancreas transplantation. Similarly, a recent study has also demonstrated an association between IENFD and vibration perception threshold; however, the majority of patients in that study also had moderate to severe neuropathy (29). Another study has shown a correlation between loss of IENF and the severity of neuropathy assessed using electrophysiology and QST (28).…”
Section: Discussionmentioning
confidence: 93%
“…Lauria et al (19) found reduced IENFD in a study of six patients with painful diabetic neuropathy compared with that in normal control subjects. In another study of patients with neuropathic pain, Sorensen et al (20) paradoxically found more severe IENFD loss compared with that in those with PLN. From this finding, they concluded that loss of IENFD cannot explain genesis of pain in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the most commonly used protocol only measures the densities of nerve fibers that penetrate the basement membrane of the epidermis; it does not take into consideration axonal branching and/or morphological changes of the nerves. In addition, current IENFD analysis has not been shown to correlate IENFD with the presence of pain in PN 15 .…”
Section: Discussionmentioning
confidence: 99%